Dietary nitrate improved exercise capacity in COPD but not blood pressure or pulmonary function: a 2 week, double-blind randomised, placebo-controlled crossover trial. (17th February 2019) - Kerley, Conor P.; James, Philip E.; McGowan, Aisling; Faul, John; Cormican, Liam
Abstract: Dietary nitrate may improve exercise tolerance in some healthy and clinical populations. Existing data regarding dietary nitrate in COPD is inconsistent. We conducted a 14d double-blind, randomised, placebo-controlled, crossover trial of daily nitrate-rich beetroot juice (BRJ; 12.9 mmol) versus nitrate-depleted BRJ (PL; 0.5 mmol). At baseline and after each condition, we assessed functional capacity (incremental shuttle walk test; ISWT), ambulatory blood pressure, pulmonary function, quality of life as well as exhaled nitric oxide (eNO), and plasma nitrate/nitrite (NOx). Eight subjects with COPD completed the trial. BRJ supplementation was associated with significantly increased NOx ( p  < .05) and a 14.6% increase in ISWT distance (+56 m, p  = .00004) as well as a trend towards increased eNO compared to PL. There was no other differences. Dietary nitrate appears to have ergogenic effect in subjects with mild-moderate COPD. This effect does not appear to be related to altering blood pressure or pulmonary function.